Primary Immunodeficiency Registry System: The Minimum Data Set Designing Phase—A Systematic Review and Quantitative Delphi Study - Saman Mohammadpour; Hassan Emami; Sima Shokri; Rafat Bagherzadeh; Soqrat Omari Shekaftik; Zanko Hosseini (Health Science Reports, 2025)
ABSTRACT Background and Aims Registries are powerful tools for data management. Designing a minimum data set as the first step in registry development helps collect relevant and efficient data. The aim of this study was to develop a minimum data set for the primary immunodeficiency registry system. Methods This cross‐sectional study was conducted at two stages in 2023. In the first stage, primary data elements were extracted from related literature. In the second stage, based on the data elements extracted from the first stage, a questionnaire was developed. Then, using the questionnaire and the Quantitative Delphi Method, the minimal data set on primary immunodeficiency was obtained from 10 asthma and allergy specialists. Results In the first stage, the initial minimum data set consisted of 198 data elements, which were categorized into two categories: administrative and clinical. Administrative data were classified into two categories: demographic and patient index. Clinical data were categorized into four categories: patient history, physical examination, tests, and diagnosis. In the second stage, eight elements were removed during the first round of Delphi. One element was removed in the second round of Delphi. In the first round of Delphi, 13 elements were recommended. In the second round of Delphi, all the recommended elements were included in the final list of the minimum data set. Finally, 202 data elements were selected as the final minimum data set. Conclusion The created primary immunodeficiency minimum data set is expected to improve decision‐making by clinicians and policymakers, and also improve scientific research in this field.